2010
DOI: 10.1093/toxsci/kfq032
|View full text |Cite
|
Sign up to set email alerts
|

Mice Treated with Chlorpyrifos or Chlorpyrifos Oxon Have Organophosphorylated Tubulin in the Brain and Disrupted Microtubule Structures, Suggesting a Role for Tubulin in Neurotoxicity Associated with Exposure to Organophosphorus Agents

Abstract: Exposure to organophosphorus (OP) agents can lead to learning and memory deficits. Disruption of axonal transport has been proposed as a possible explanation. Microtubules are an essential component of axonal transport. In vitro studies have demonstrated that OP agents react with tubulin and disrupt the structure of microtubules. Our goal was to determine whether in vivo exposure affects microtubule structure. One group of mice was treated daily for 14 days with a dose of chlorpyrifos that did not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 50 publications
2
78
0
1
Order By: Relevance
“…For example, using a spectrophotometric method, Prendergast et al (2007) demonstrated that chlorpyrifos-oxon inhibited the polymerization of tubulin, and (using organotypic slice cultures of rodent brain and histologic methods) caused a marked decrease in the concentration of microtubule associated protein-2. Moreover, using atomic force microscopy, Lockridge and colleagues observed that chlorpyrifosoxon disrupted tubulin polymerization, and further (using mass spectrometry) that chlorpyrifos-oxon covalently binds to tubulin, an effect that may explain the disruptions in tubulin polymerization Jiang et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…For example, using a spectrophotometric method, Prendergast et al (2007) demonstrated that chlorpyrifos-oxon inhibited the polymerization of tubulin, and (using organotypic slice cultures of rodent brain and histologic methods) caused a marked decrease in the concentration of microtubule associated protein-2. Moreover, using atomic force microscopy, Lockridge and colleagues observed that chlorpyrifosoxon disrupted tubulin polymerization, and further (using mass spectrometry) that chlorpyrifos-oxon covalently binds to tubulin, an effect that may explain the disruptions in tubulin polymerization Jiang et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported previous spectrophotometric studies and experiments using atomic force microscopy ) where CPF-oxon was found to disrupt tubulin polymerization. Interestingly CPF-oxon has also been shown to covalently bind to tubulin, an effect that may explain the disruptions in tubulin polymerization (Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether a nontoxic dose can form protein adducts in animals, Jiang et al 39 treated mice with 3 mg/kg chlorpyrifos (parent compound; not the oxon) daily for 14 days. The pesticide chlorpyrifos is bioactivated through oxidative desulfuration catalyzed by cytochrome P450 enzymes to form CPO.…”
Section: Discussionmentioning
confidence: 99%